Minat Pelajar Muslim Menggunakan Mobile Banking - Syobri Tri Rahmansyah; Heri Sudarsono; Sarastri Mumpuni Ruchba; Indah Susantun (Jurnal Ilmiah Ekonomi Islam, 2023)
The purpose of this research is to analyze the intention of a Muslim student in using mobile banking using the Unifield Theory of Acceptance and Use of Technology 2 (UTAUT2) model approach. This research was conducted in August - September 2022 and the data source for this research was obtained using a survey method with a questionnaire distributed via broadcast to social media. This study uses a quantitative data processing method using SEM PLS (Partial Least Square) analysis with the statistical tool SmartPLS 3.3. The respondents in this study were students on the island of Java who had used mobile banking for at least 1 year. the variables used in this study are Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Hedonic Motivation (HM), Facilitating Conditions (FC), Religiosity (RE), Habit (HB), Behavior Intention ( BI), Use behavior (UB). The results of this study indicate that HB, HM, and RE, have a significant influence on the intention to use mobile banking BI. While EE, FC, PE, and SI are not accepted and have no significant effect on the intention to use mobile banking BI, so that the HB, and intention using BI, has a significant effect on using mobile banking UB while FC is not accepted and has no significant effect on using mobile banking